Preventing a Thought from Coming to Mind Elicits Increased Right Frontal Beta Just as Stopping Action Does. (26th February 2019) - Castiglione, Anna; Wagner, Johanna; Anderson, Michael; Aron, Adam R
Abstract: In the stop-signal task, an electrophysiological signature of action-stopping is increased early right frontal beta band power for successful vs. failed stop trials. Here we tested whether the requirement to stop an unwanted thought from coming to mind also elicits this signature. We recorded scalp EEG during a Think/No-Think task and a subsequent stop signal task in 42 participants. In the Think/No-Think task, participants first learned word pairs. In a second phase, they received the left-hand word as a reminder and were cued either to retrieve the associated right-hand word ("Think") or to stop retrieval ("No-Think"). At the end of each trial, participants reported whether they had experienced an intrusion of the associated memory. Finally, they received the left-hand reminder word and were asked to recall its associated target. Behaviorally, there was worse final recall for items in the No-Think condition, and decreased intrusions with practice for No-Think trials. For EEG, we reproduced increased early right frontal beta power for successful vs. failed action stopping. Critically, No-Think trials also elicited increased early right frontal beta power and this was stronger for trials without intrusion. These results suggest that preventing a thought from coming to mind also recruits fast prefrontal stopping.